EXPRESSION PROFILE OF MOLECULAR CIRCADIAN CLOCK GENES PREDICTS RISK STRATIFICATION IN ACUTE MYELOID LEUKEMIA - M Brandão; SCG Lima; DT Covas; LEB Souza (Hematology, Transfusion and Cell Therapy, 2023)
Objectives: Acute Myeloid Leukemia (AML) is a complex and heterogeneous disease characterized by the blockage of blood cell maturation, leading to uncontrolled proliferation of immature malignant cells. Based on cytogenetic characteristics, AML can be classified into three prognostic groups: favorable, intermediate, and adverse. Recently, studies have revealed the importance of the molecular circadian clock, in cancer development, and progression. The main positive regulators of the molecular circadian clock are the dimers formed by BMAL1 and CLOCK transcription factors, which activate the expression of negative regulators (e.g. PERs, CRYs, RORs and REV-ERBs) that in turn inhibit the expression or transcriptional activity of BMAL1/CLOCK complexes. These clock proteins can also promote the transcription of several other “clock controlled genes” involved in diverse cellular processes. For example, clock genes regulate the expression of the cell cycle checkpoint protein p21CIP1, control mitochondrial function, and modulate the activity of sensors of DNA damage, such as ATM. Thus, it is not surprising that disruption of the molecular clock has been associated with numerous metabolic disorders and cancer. Thus, the objective of this study was to interrogate whether the expression profile of core molecular circadian clock genes are associated with the cytogenetic prognostic categories in AML. Materials and Methods: This study used in silico analyses of data available on the R2 database: Genomics Analysis and Visualization Platform. The database of Acute Myeloid Leukemia deposited in 2015, “Tumor acute Myeloid Leukemia - TCGA - 173 - rsem - tcgars,” was selected. We evaluated the expression of 13 genes associated with the circadian clock: CLOCK, BMAL1, BMAL2, PER1, PER2, PER3, CRY1, CRY2, RORα, RORβ, RORγ, NR1D1, and NR1D2. The Anderson-Darling normality test was performed for all analyzed data. Gene expression was association with cytogenetic prognostic classification was done using the Kruskal-Wallis test. Overall survival (event = death) was evaluated with Kaplan-Meier curves and log-rank test, according to the cytogenetic prognostic classification (favorable, intermediate, and adverse). Results: As a validation process, we confirmed that the intermediate and adverse risk groups showed lower overall survival (p = 0.0011) when compared to the favorable risk group. Notably, expression levels of BMAL1 (p < 0,0001), PER3 (p = 0.0012), and NR1D1 (p = 0.0139) revealed a significant association with a more unfavorable prognosis for AML. These findings indicate that high expression of these genes is related to a worse clinical outcome. The expression levels of remaining clock genes were not associated with risk groups defined by cytogenetic classification for AML. Conclusions: The results suggest that these three core clock genes (BMAL1, PER3 and NR1D1) are prognostic markers for AML, providing new perspectives for risk stratification and potential therapeutic targets.